2013
DOI: 10.1530/eje-13-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medical therapies for acromegaly on glucose metabolism

Abstract: Objective: Abnormalities of glucose metabolism are common findings of acromegaly. However, robust evidence on whether therapy with somatostatin analogs (SSAs) or pegvisomant (PEG) differently affects glucose metabolism is lacking. The purpose of this study was to evaluate the effects of therapy with SSAs, PEG, or their combination on glucose metabolism in a large series of acromegalic patients. Design: This was a historical-prospective study. Among 50 consecutive acromegalic patients under SSA therapy, acromeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 38 publications
1
71
3
7
Order By: Relevance
“…In contrast to SSA, PEG decreases fasting plasma glucose (Urbani et al 2013) and improves glucose tolerance (Colao et al 2006) and insulin sensitivity (Schreiber et al 2007). Switching from SSA to PEG significantly improves diabetes control in diabetic ACM cases .…”
Section: Medical Treatmentmentioning
confidence: 99%
“…In contrast to SSA, PEG decreases fasting plasma glucose (Urbani et al 2013) and improves glucose tolerance (Colao et al 2006) and insulin sensitivity (Schreiber et al 2007). Switching from SSA to PEG significantly improves diabetes control in diabetic ACM cases .…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Исследование механизмов развития НУО при акромегалии в зави-симости от терапии показало, что как после хирур-гического, так и на фоне медикаментозного лечения акромегалии происходит снижение инсулиноре-зистности печени (HOMA-IR) и инсулинзависимых тканей в целом (Matsuda). Данные результаты согла-суются с результатами других исследований и свиде-тельствуют о снижении инсулинорезистентности печени и периферических инсулинзависимых тка-ней на фоне хирургического и медикаментозного лечения акромегалии [7,10,11].…”
Section: Discussionunclassified
“…[2,[4][5][6] и специфические для акромегалии (длительность и *e-mail: trigolosova_ira@mail.ru © Коллектив авторов, 2015 активность заболевания, проводимое лечение и т.п.) [2,7,8]. Основной метод лечения акромегалии -хирургический, который, по данным современных исследований [9,10], является не только наиболее эффективным, но и оказывает положительное влия-ние на состояние углеводного обмена.…”
unclassified
See 1 more Smart Citation
“…2) SSA treatment has a divergent effect on glucose metabolism: a positive one lowering GH/IGF-I levels, decreasing insulin resistance and a negative effect suppressing insulin secretion. 35,36 A recent meta-analysis showed that SSA have a minor impact on glucose homeostasis in acromegaly, 36 although some controversy persists, 37 and 3) PEG has positive effects on glucose metabolism in acromegaly. [38][39][40][41][42] PEG does not exert any direct effect on pancreatic β-cell function and unlike SSA it does not suppress insulin secretion.…”
Section: Efficacy Of Peg In Clinical Studiesmentioning
confidence: 99%